The Relationship Between Competitive Intelligence and Entrepreneurial Performance By Centralizing Strategic Vigilance: Field study of a sample of National colleges in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of this study is to highlight the relationship between competitive intelligence and Entrepreneurial Performance by centralizing the strategic vigilance of a sample of civil faculties in Baghdad. The sample of the study was targeted at 10 Iraqi civil colleges, which consisted of (133) members of the faculty council of the faculties, the search data was collected using the questionnaire form as the main research tool. The results showed that the correlation and influence of competitive intelligence and strategic vigilance in the Entrepreneurial Performance, as well as the role of strategic vigilance as an intermediate variable between competitive intelligence and Entrepreneurial Performance.